2000
DOI: 10.1002/(sici)1096-987x(20000715)21:9<763::aid-jcc5>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Improved treatment of cyclic ?-amino acids and successful prediction of ?-peptide secondary structure using a modified force field: AMBER*C

Abstract: We added parameters to the AMBER* force field to model cyclic β‐amino acid derivatives more accurately within the commonly used MacroModel program. In an effort to generate an improved treatment of cyclohexane and cyclopentane conformational preferences, carbon–carbon torsional parameters were modified and incorporated into a force field we call AMBER*C. Simulation of trans‐2‐aminocyclohexanecarboxylic acid (trans‐ACHC) and trans‐2‐aminocyclopentanecarboxylic acid (trans‐ACPC) derivatives using AMBER*C produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 66 publications
1
30
0
Order By: Relevance
“…Conformational profiles of the cyclic peptides were investigated by Macromodel's LLMOD procedure of Kolossváry (58,66–68) using the energy minimization parameters as described above. A total of 10 000 search steps were performed and the conformations with energy difference of 50 kJ/mol from the global minimum were saved.…”
Section: Computational Proceduresmentioning
confidence: 99%
“…Conformational profiles of the cyclic peptides were investigated by Macromodel's LLMOD procedure of Kolossváry (58,66–68) using the energy minimization parameters as described above. A total of 10 000 search steps were performed and the conformations with energy difference of 50 kJ/mol from the global minimum were saved.…”
Section: Computational Proceduresmentioning
confidence: 99%
“…It was found that simulations are quite sensitive to the inclusion of long-range electrostatic interactions [18] [19]. Christianson et al also studied the folding process of b-peptides made of trans-2-aminocyclopentanecarboxylic acid and trans-2-aminocyclohexane carboxylic acid derivatives by using a modified AMBER force field [20].…”
mentioning
confidence: 99%
“…are possible. Qualitative comparison of the amide A region of the IR spectra in CH 2 Cl 2 of the N ‐isobutyryl methylamide derivatives of trans ‐Achc and trans ‐Acpc indicated that the trans ‐Acpc derivative is more prone to C 8 IHB formation than the trans ‐Achc derivative21. The NH stretching contribution to the amide A band of the C 8 H‐bonded derivatives of trans ‐Achc and trans ‐Acpc appears at 3357 and 3306 cm −1 , respectively, suggesting that the CO and HN in the trans ‐Achc model are not oriented as favorable for a strong hydrogen bond as in the trans ‐Acpc derivative.…”
Section: Introductionmentioning
confidence: 99%